EVALUATION OF MSME SALES AND BILLING CONTROL THROUGH THE UTILIZATION OF QRIS AND MARKETPLACE: A CASE STUDY OF ES TELER 88 MAKASSAR - Hasman , Hasman; Maylani Putri. B, Yuyun; Arifin, Rezky Awaliah Ramadhana; Junaedi, Alifia Salzabila; Zaimar, Fina Ruzika (Indo-Fintech Intellectuals: Journal of Economics and Business, 2025)
Sales and collection control plays a vital role for Micro, Small, and Medium Enterprises (MSMEs) in maintaining cash flow and ensuring business sustainability. This study evaluates the effectiveness of sales and collection control through the use of Quick Response Code Indonesian Standard (QRIS) and marketplace at MSME Es Teler 88 Makassar using the Committee of Sponsoring Organizations of the Treadway Commission (COSO) framework. The research applies a descriptive qualitative case study approach with observation, interview, and documentation methods. The results show that implementing QRIS and marketplace enhances transaction accuracy, accelerates billing, and minimizes uncollectible receivables. The integration of financial technology enables automated record-keeping, real-time cash flow monitoring, and more orderly reconciliation than manual methods. Analysis through the five COSO components confirms that digital transactions not only simplify payments but also strengthen internal controls through built-in mechanisms. Therefore, using QRIS and marketplace serves as an effective strategy for MSMEs to improve operational efficiency, maintain liquidity, and support more accurate financial decision-making.